Communication between cultures - Samovar, Larry A.; McDaniel, Edwin R.; Porter, Richard E.; Roy, Carolyn S. (Wardsworth/Cengage Learning, 2013)
From the Publisher: Communication between cultures helps you develop practical skills for improving your communicaiton with people from other cultures and provides a unique focus on the deep structure of culture, emphasizing the roles that family, religion, and history play in intercultural communication. The text book is divided into four interrelated parts: Part I introduces the study of communication and culture; Part II focuses on the ability of culture to shape and modify our view of reality; Part III puts the theory of intercultural communication into practice; and Part IV converts knowledge into action